Monetary tightening cycles and the predictability of economic activity - Tobias Adrian; Arturo Estrella (Federal Reserve Bank of New York, 2009)
Eleven of fourteen monetary tightening cycles since 1955 were followed by increases in unemployment; three were not. The term spread at the end of these cycles discriminates almost perfectly between subsequent outcomes, but levels of nominal or real interest rates, as well as other interest rate spreads, generally do not.
Keywords: E44; E52; G17; 330; Monetary policy; interest rates; term structure; discriminant analysis; logit